Effect of Sand Grain Size on Spontaneous Imbibition of Surfactant Solution - Pri Agung Rakhmanto; Listiana Satiawati; Rini Setiati; Asri Nugrahanti; Sonny Irawan (Journal of Earth Energy Science, Engineering, and Technology, 2021)
In spontaneous imbibition researches, surfactant has been employed to control interfacial tension (IFT) and wettability. In this paper, the evaluation of grain size effect on spontaneous imbibition of surfactant solution is presented. In this work, the synthetic porous media (sand packs) with uniform and non-uniform grain size from 30 mesh to 100 mesh were made. The porous media were initially saturated by oil. Then they were immersed in brine with salinity of 62 to 40,000 ppm for 24 hours. After that, the porous media were immersed in surfactant solution with concentration of 0.2% for another 24 hours. The total oil recovery during these treatments was measured. The experiment was separated into three parts in order to investigate the effect of uniform grains, non-uniform grains, and salinity in spontaneous imbibition. The results show that grain size and porosity were proportional to oil recovery. In the case of porous media with uniform grain size, the effect of grain size on recovery factor is stronger than that of porosity. Meanwhile the salinity has an the optimum condition for a maximum recovery factor. In this study, it happened at salinity of 20,000 ppm. Oil recovery factors observed in this study ranged from 66.7% to 91.1%.